First Phylogenetic Treatment of Apple Cucumber (Family Cucurbitaceae) from Indonesia Utilizing DNA Variation of Internal Transcibed Spacer Region - Topik Hidayat; Nurcahyo Widyodaru Saputro; Miftakhul Bakhrir Rozaq Khamid; Fawzy Muhammad Bayfurqon (Bogor Agricultural University, Indonesia, 2021)
Cucurbitaceae is one of the largest family in Angiosperm in which the most member of this family is important fruit crops in Indonesia such as Cucumber, Melon, Watermelon, and Apple Cucumber. In particular, Apple Cucumber, currently attracts attention to many researchers due to its phylogeneticand taxonomic problem. In term of its appearance, the fruit looks like an apple but the taste is melon. The purpose of this study was to elucidatephylogenetic relationship between Apple Cucumber and other species of Cucurbitaceae based on variation of DNA sequences derived from internal transcribed spacer (ITS) region. As many as six individuals of Apple Cucumber collected from Karawang, Jember, and Aceh were examined. The ITS sequences of some species of family Cucurbitaceae were retrieved from GenBank, and put them in the analysis. Phylogenetic analysis based on parsimony method with using Begoniaas outgroup reveals that Apple Cucumber are nested in the same clade as Melon (Cucumis melo) with high bootstrap value (100%), suggesting that Apple Cucumber is under the same species as Melon. However, on the basis of morphological characters of fruit, apple cucumber is different with that of Melon. This considerably first phylogenetics treatment provides fundamental knowledge for establishing a subspecies of Melon.